An outline of english grammar with exercises and answer key - Stern, George (Learners Singapore, 2002)
An Outline of English Grammar with Exercises and Answer Key offers a comprehensive guide to English grammar, featuring clear explanations, practical exercises, and solutions to reinforce learning.